Fifteen years of human development reports, 1990-2004 - United Nations Development Programme (New York : Human Development Report Ofice, United Nations Develop ment Programme, 2005)
This CD-ROM includes the complete, searchable texts of 15 Human Deve lopment Reports (HDR) 1990-2004, along with the data from indicator tab les of HDR 2004.
Interface and software developed by Summit Tech. and teh CD-ROM dist ributed by UN Publications.
Text.
System requirements: Pentium class processor, Microsoft Windows 95, 98, NT 4.0, 2000 or XP, 64 MB RAM and optional requirements such as Ado de Acrobat Reader and Microsoft Excel 97.
The CD-ROM is distributed in English and French.
Keywords: Personnel management; Manpower policy